Residue 49 of AtMinD1 Plays a Key Role in the Guidance of Chloroplast Division by Regulating the ARC6-AtMinD1 Interaction - Zhang, Yanhua; Zhang, Xiaochen; Cui, Huanshuo; Ma, Xinzhu; Hu, Guipeng; Wei, Jing; He, Yikun; Hu, Yong (Frontiers in Plant Science, 2021)
Chloroplasts evolved from a free-living cyanobacterium through endosymbiosis. Similar to bacterial cell division, chloroplasts replicate by binary fission, which is controlled by the Min (Minicell) system through confining FtsZ ring formation at the mid-chloroplast division site. MinD, one of the most important members of the Min system, regulates the placement of the division site in plants and works cooperatively with MinE, ARC3, and MCD1. The loss of MinD function results in the asymmetric division of chloroplasts. In this study, we isolated one large dumbbell-shaped and asymmetric division chloroplast Arabidopsis mutant cdm75 (Chloroplast Division Mutant 75) that contains a missense mutation, changing the arginine at residue 49 to a histidine (R49H), and this mutant point is located in the NCTS (N-terminal Conserved Terrestrial Sequence) motif of AtMinD1, which is only typically found in terrestrial plants. This study provides sufficient evidence to prove that residues 1–49 of AtMinD1 are transferred into the chloroplast, and that the R49H mutation does not affect the function of the AtMinD1 chloroplast transit peptide. Subsequently, we showed that the point mutation of R49H could remove the punctate structure caused by residues 1–62 of the AtMinD1 sequence in the chloroplast, suggesting that the arginine at residue 49 (Arg49) is essential for localizing the punctate structure of AtMinD11-62 on the chloroplast envelope. Unexpectedly, we found that AtMinD1 could interact directly with ARC6, and that the R49H mutation could prevent not only the previously observed interaction between AtMinD1 and MCD1 but also the interaction between AtMinD1 and ARC6. Thus, we believe that these results show that the AtMinD1 NCTS motif is required for their protein interaction. Collectively, our results show that AtMinD1 can guide the placement of the division site to the mid-chloroplast through its direct interaction with ARC6 and reveal the important role of AtMinD1 in regulating the AtMinD1-ARC6 interaction.